PENGARUH KUALITAS, KEMUDAHAN PENGGUNAAN, KECEPATAN AKSES DAN KEAMANAN SIA TERHADAP KINERJA KARYAWAN PT. BOOKING INDONESIA - Budiawan, I Made Dwi Darma; Agung Suaryana, I Gusti Ngurah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.05.TAHUN.2023DO - 10.24843/EEB.2023.v12.i05.p08, 2023)
The phenomenon that occurs at booking.com Indonesia is where workers still do not show maximum performance such as late reporting. The purpose of this study was to determine the effect of quality, ease of use, speed of access and security of accounting information systems on the performance of employees of PT. Indonesian Bookings. This research method uses quantitative data analysis techniques. The population of this study were all employees of PT. Booking Indonesia in Bali as many as 50 employees. The method of determining the sample using a saturated sample. The number of research samples is 40 employees of PT. Booking Indonesia Bali. Data analysis using multiple linear regression analysis technique. The results showed that there was a positive influence on the quality of AIS on employee performance at PT. Booking.com Indonesia, there is a positive influence on the ease of use of SIA on employee performance at PT. Booking.com Indonesia, there is a positive effect of SIA access speed on employee performance at PT. Booking.com Indonesia and there is a positive effect of SIA security on employee performance at PT. Booking.com Indonesia